Cortisol Level Related to Depression in Women with Endometriosis - Adnan Abadi; Aria Indrabrata; Iskandar Zulqarnain; Theodorus; Abdullah Sahab; Kemas Yusuf Effendi; Heriyadi Manan; Fatimah Usman; Awan Nurtjahyo; Cindy Kesty (HM Publisher, 2022)
Background: Several main symptoms of endometriosis can lead to physical and psychological stress and also hormonal disturbances as the result of prolonged stress. Cortisol was associated with the onset of depression. This study aimed to determine the relationship between cortisol levels and depression in women with endometriosis at the Department of Obstetrics and Gynecology at Dr. Mohammad Hoesin General Hospital (RSMH) Palembang. Methods: A cross-sectional study was performed at the Reproductive Endocrinology and Infertility outpatient clinic and inpatient ward, Department of Obstetrics and Gynecology at Dr. Mohammad Hoesin General Hospital Palembang, from January to November 2020. There were 74 samples of endometriosis patients who met the inclusion criteria. The blood cortisol level was examined using the ELISA method. The determination of depression level was performed by filling out the Beck Depression Inventory questionnaire. Data were analyzed using SPSS version 22.0. Results: Seventy-four samples met the inclusion criteria. As many as 44 patients (59.5%) without depression, 20 patients (27%) with mild depression, 8 patients (10.8%) with moderate depression, and only 2 patients (2.7%) with severe depression. There were no differences in age, marital status, parity, menstrual cycle, and duration of treatment between endometriosis patients with and without depression (p > 0.05). There was a significant difference in cortisol levels between endometriosis patients with and without depression (p = 0.017). Endometriosis patients with cortisol levels ≤ 7.4 mg/dl were three times more at risk of depression than endometriosis patients with cortisol levels > 7.4 mg/dl. In addition, there was a significant relationship between cortisol level and depression status (OR = 3.023 (95% CI 1.153–7.942; p = 0.041). This study also found a significantly low negative correlation between cortisol levels and BDI scores (r = -0.249; p = 0.032). Conclusion: There was a significant relationship between serum cortisol levels and depression in women with endometriosis. Endometriosis patients with depression had significantly lower cortisol levels than endometriosis patients without depression.